Simplified diffusion model of gas hydrate formation from ice. (February 2021) - Vlasov, Valeriy A.
Highlights: A kinetic model of gas hydrate formation from ice is developed. The temperature dependence of CH4 diffusivity in CH4 hydrate is determined. The temperature dependence of CO2 diffusivity in CO2 hydrate is determined. There are no pores in the volume of gas hydrate formed from ice. The higher the temperature and CH4 pressure are, the more intensively that CH4 hydrate grows from ice. Abstract: A kinetic model of gas hydrate formation from ice is presented. This model takes into account that the kinetics of gas hydrate formation from ice is limited only by the rate of diffusion of the gas through the gas hydrate layer. The problems of gas hydrate formation from a spherical ice particle, gas hydrate formation from a flat ice layer, and gas hydrate formation from cylindrical ice are considered separately. For each of these problems, a solution in the framework of a quasi-stationary approximation is obtained. The calculated data are compared with available experimental data on the kinetics of formation of methane hydrate and carbon dioxide hydrate from ice powder. From this comparison, the temperature dependence of the molecular diffusion coefficient of methane in methane hydrate and the temperature dependence of the molecular diffusion coefficient of carbon dioxide in carbon dioxide hydrate were determined: D C H 4 [ m 2 s − 1 ] = exp ( − 12.8 − 6242 / T [ K ] ) and D C O 2 [ m 2 s − 1 ] = exp ( − 30.0 − 1179 / T [ K ] ) . In addition, from this comparison, it was found that the porous structure is absent in the volume of gas hydrate formed from ice. Taking into account the determined temperature dependence of the molecular diffusion coefficient of methane in methane hydrate, it is found that methane hydrate formation from ice proceeds more intensively the closer the temperature is to the quadruple point temperature and the higher the methane pressure is.